(3JfHjg GdZGadjf hEjbGX GdfGFejfs - (3GdSeQbfOj, CHh GddjK, EeGe GdgOi, fUQ Hf eMeO Hf CMeO Hf EHQGgje, (B373 (3g`s
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3ESMGb GdLhRLGfj KfG OhO Hf EHQGgje KfG fhM Hf CHj eQje Yf ebGJd Hf MjGf Yf YcQeI Yf GHf YHGS QVj Gddg Yfge Cf QShd Gddg Udi Gddg Ydjg hSde PcQ HGH GdJhHIs
(3BNQgG (B:s
(3hUGMH GdCNOhO, hUGMH LQjL, hUGMH jhSa UdhGJ Gddg hSdGeg Ydjg hgh bhdg JYGdi (B{(3hTgO TGgO ef CgdgG(B}s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 8 / 27s
(3eYLe GdeDdajf(B: 4 / 24s
(3cTa GdXfhf(B: 1 / 487s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs